Geographies of emotion in university spaces: Sole parent postgraduate subjects negotiating ‘child-free’ educational boundaries - Hook, Genine A. (Emotion, space and society, 2016)
In this paper I explore the emotional geographies of Australian universities which tend to (re)produce higher education spaces as ‘child-free’. Drawing on Butler's theoretical tool of performativity and Ahmed's conceptual use of emotion, I seek to examine how educable sole parent students are constituted in university spaces largely prescribed as child-free. By examining some experiences of sole parent postgraduates, I aim to demonstrate some of the ways emotions work to reinscribe and regulate academic recognisability through boundary maintenance of university spatial arrangements. The sole parent postgraduate experiences I draw from in this paper illustrate that educational spaces are not passive; they are productive and regulatory. Speech acts that (re)produce university spaces as ‘child-free’ have particular implications for sole parent postgraduates who often experience un-relenting responsibilities of child-care. Sole parent postgraduates in this study shared their experiences of emotional bonds with their children as often in conflict with their sense of belonging and engagement with university spaces and practices. Butler's theory of performativity is useful to examine some of the ways the conflict between sole parent childcare and postgraduate education is experienced and the potential for productive manoeuvres by sole parents to disrupt and re-work the emotional geographies within Australian higher education spaces.